2022
DOI: 10.1155/2022/5387928
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast Agent and Molecular Imaging Meta-Analysis of the Clinical Effect of Intelligent Image Sensor Combined with Visual Training in the Treatment of Children with Intermittent Exotropia in China

Abstract: At present, the main treatment for strabismus is still surgical treatment, but there is no unified standard for the evaluation of the timing of surgery. This study mainly explores the clinical effects of using meta-analysis of intelligent image sensors combined with visual training to treat children with intermittent exotropia. Cochrane systematic reviews collect, evaluate, and synthesize an increasing number of original clinical research results to obtain the comprehensive effect of relevant interventions, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%